Pengaruh Bercerita Menggunakan Visualisasi Boneka Tangan Terhadap Kemampuan Komunikasi Bicara Pada Anak Autisme - Ni Nyoman Soma Wati; Si Luh Nyoman Alit Nuryani; Ni Luh Putu Devhy (STIKES Karya Husada Kediri, 2020)
Autism is a developmental disorder that occurs in children where children experience self-closing conditions. Disorders in children with autism can result in children experiencing limitations in terms of communication, social interaction and behavior. Communication problems in speaking experienced by children with autism is one problem that must be addressed because communication is one of the things that are needed by humans as social beings. Visual media means all the props that are used in the learning process that can be enjoyed through the five senses. The purpose of this study was to find out the effect of storytelling using hand puppet visualization on speech communication skills in children with autism at the Denpasar City Autism Service Center. This study uses a quasi-experimental design with pretest-posttest control group design and uses simple random sampling method. The number of samples used were 39 respondents, 20 respondents in the treatment group and 19 respondents in the control group. Data analysis using the Wilcoxon Signed Ranks Test and Mann Whitney Test. Ho was rejected, so it can be concluded that there is an effect of storytelling using hand puppet visualization of speech communication skills in children with autism at Denpasar City Autism Service Center.